Melting Time and Fe Content of Soybean Ice Cream by Utilizing Moringa Flour, Southeast Sulawesi Varieties, Indonesia - Habib Ihsan Mowuta Ihsan Mowuta; Riska Mayangsari (KLASICS, 2022)
Abstract. Adolescents are a high-risk group for anemia. The prevalence of anemia in adolescents was 32% in 2018. One of the risk factors for anemia is the low intake of iron (Fe). Local food diversification is an effort to increase iron intake, one of which is by making ice cream using Moringa and soybean flour. Moringa leaves contain higher iron than other vegetables, namely 17.2 mg / 100 g. Ice cream is a snack that is loved by all levels of society. This study aims to determine the melting time and fe content of ice cream by utilizing Moringa leaf flour. This study used a one-factor completely randomized design (CRD). The research data were analyzed descriptively. The results of this study indicate that the ice cream with the addition of 5 gram of Moringa leaf flour has an average melting time of 49,18 minutes, and the laboratory results show the ice cream content is 0.114 mg / L and the addition 10 grams of Moringa leaf flour has an average melting speed of 58.26 minutes, and the laboratory results show the ice cream content is 0.135 mg / L. The results of this study indicate that the ice cream with the addition of 10 grams of Moringa leaf flour has an average melting speed of 58.26 minutes, and the laboratory results show the ice cream content is 0.135 mg / L. Soybean ice cream with the use of Moringa leaf flour can be used as an alternative healthy snack for adolescents.